In vitro antioxidant, anti-inflammatory, and anticancer activities of mixture Thai medicinal plants - Suchada Jongrungraungchok; Fameera Madaka; Thaniya Wunnakup; Teeratad Sudsai; Chanamon Pongphaew; Thanapat Songsak; Nalinee Pradubyat (BMC, 2023)
Abstract Background The phytochemical study of medicinal plants is rapidly gaining popularity with many pharmacologic effects. This study aims to determine the antioxidant capacity as well as anticancer and antimigration activities of Clear belongs Plus extract (CBL-P) which consisted of five medicinal plants namely, Alpinia galanga, Piper nigrum, Citrus aurantifolia, Tiliacora triandra, and Cannabis sativa on human colon cancer cells SW620 and HCT116 cell lines, and human non-small cell lung cancer cells A549 and NCI-H460 cell lines. Methods In this study the dried-plant powder was extracted using 90% ethanol. Additionally, CBL-P was studied antioxidative activity via DPPH and ABTS assays and anti-inflammatory activities using nitric oxide assay using Griess reaction. Antiproliferation and antimigration of CBL-P were investigated using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) and scratch assay. Results The results showed that CBL-P had potent antiproliferative activity with IC50 values in a concentration- and time-dependent manners for all four cell lines. CBL-P also possessed potent antimigration activity against all studied cancer cells. CBL-P demonstrated antimigration activity on four different types of cancer cells (A549, NCI-H460, HCT116, and SW620) after 48 h of incubation, with the greatest effect seen at the highest concentration tested (15 μg/mL) in A549 cells (10.23% of wound closure) and NCI-H460 cells (9.16% of wound closure). CBL-P was also effective in reducing migration in HCT116 and SW620 cells, with a range of closure area from 10-50%. In addition, CBL-P had antioxidant activity with IC50 values of 8.549 ± 0.241 mg/mL and 2.673 ± 0.437 mg/mL for DPPH and ABTS assays, respectively. CBL-P also showed anti-inflammatory activity with the best inhibitory activity on NO production at a concentration of 40 μg/mL. Conclusion In conclusion, the mixture extract possessed antioxidant and anti-inflammatory activity. Furthermore, the mixture plant extract significantly exhibited antiproliferative and antimigration activities on SW620, HCT116, A549, and NCI-H460 cells (P ≤ 0.05). Taken together, our results suggest that medicinal plants may have synergistic effects that could potentially enhance the effectiveness of cancer treatment when used as adjuvants. These findings provide a solid scientific foundation for future efforts to explore the mechanism of action.